2021
DOI: 10.1038/s42003-021-02675-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of compound resting membrane potentials of cell cultures with ratiometric genetically encoded voltage indicators

Abstract: The cellular resting membrane potential (Vm) not only determines electrical responsiveness of excitable cells but also plays pivotal roles in non-excitable cells, mediating membrane transport, cell-cycle progression, and tumorigenesis. Studying these processes requires estimation of Vm, ideally over long periods of time. Here, we introduce two ratiometric genetically encoded Vm indicators, rArc and rASAP, and imaging and analysis procedures for measuring differences in average resting Vm between cell groups. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Fusion of mKate2 to a potentiometric GEVI is not only suited to determine the molecular brightness of a sensor molecule but also allows for absolute V m calibration, as we have shown previously (35). However, we observed that the fusion of mKate2 reduced the expression level of the sensor by a factor of 3.1 (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Fusion of mKate2 to a potentiometric GEVI is not only suited to determine the molecular brightness of a sensor molecule but also allows for absolute V m calibration, as we have shown previously (35). However, we observed that the fusion of mKate2 reduced the expression level of the sensor by a factor of 3.1 (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…As a proof of concept, we recorded F 480 /F 400 from HEK293T cells stably expressing rEstus. We treated cells with 1 μM gramicidin, an ionophore that short-circuits the plasma membrane when integrated (35). The difference in F 480 /F 400 between control cells and those treated with gramicidin was readily apparent on a single-cell level (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, for such interventions to be effective at targeting the Vm, the wider context of tissue-, organ-wide and long-range endogenous electric fields needs to be considered 40 , as well as the possibility that cancer cells in certain tumor types may function as an electrical syncytium via gapjunctional communication 41 . A barrier to progression in this area remains the absence of reliable methods to accurately quantify small Vm changes in vitro and in vivo, although encouraging progress is now being made in this regard 42,43 . In addition, further work is required to address whether the Vm-dependent effects reported thus far are generalisable across different tumor types.…”
Section: Future Perspectives: Therapeutic Vm Targetingmentioning
confidence: 99%